Diverse metabolic response of cancer cells treated with a (213)Bi-anti-EGFR-immunoconjugate - Feuerecker, Benedikt (Sci Rep, 2021)
Evaluation of treatment response is among the major challenges in modern oncology. We herein used a monoclonal antibody targeting the EGF receptor (EGFR) labelled with the alpha emitter (213)Bi ((213)Bi-anti-EGFR-MAb). EJ28Luc (bladder) and LN18 (glioma) cancer cells, both overexpressing EGFR, were incubated for 3 h with the radioimmunoconjugate. To assess the responses in the core carbon metabolism upon this treatment, these cancer cell lines were subsequently cultivated for 18 h in the presence of [U-(13)C(6)]glucose. (13)C-enrichment and isotopologue profiles of key amino acids were monitored by gas chromatography–mass spectrometry (GC/MS), in order to monitor the impacts of the radionuclide-treatment upon glucose metabolism. In comparison to untreated controls, treatment of EJ28Luc cells with (213)Bi-anti-EGFR-MAb resulted in a significantly decreased incorporation of (13)C from [U-(13)C(6)]glucose into alanine, aspartate, glutamate, glycine, proline and serine. In sharp contrast, the same amino acids did not display less (13)C-enrichments during treatment of the LN18 cells. The data indicate early treatment response of the bladder cancer cells, but not of the glioma cells though cell lines were killed following (213)Bi-anti-EGFR-MAb treatment. The pilot study shows that the (13)C-labelling approach is a valid tool to assess the responsiveness of cancer cells upon radionuclide-treatment in considerable metabolic detail.